Current Situation and Prospect of Large-scale Wind Turbine Drive-train Test System at Home and Abroad - HU Shuju; MENG Yanfeng; SONG Bin; MA Rui; LI Fenglin; DENG Ya (Kongzhi Yu Xinxi Jishu)
Drive-train ground test of large-scale wind turbine is an important means to speed up the R & D process of technology and ensure the performance and reliability of wind power equipment. In recent years, much attention have been paid in wind power developed countries to the construction of wind turbine drive-train ground testing system, but there is no similar public testing system at home. Firstly, the high-power wind turbine drive-train ground testing systems built in the United States, Denmark, Germany and other countries were summarized, and the capability of the testing systems were emphasized. Then, the commonness of these testing systems was analyzed from the aspects of construction, capability and management. Secondly, the corresponding domestic situation was also illustrated, the relevant planning and carried out research layout were introduced. Finally, future of the drive-train ground test of large-scale wind turbine in China was prospected and suggestions of development and construction for the public test system were proposed considering the domestic current and future development requirements of wind power technology and industry.